Scoping Review of PTSD Treatments for Natural Disaster Survivors - Arjun Nanduri; Marlon Vasquez; Savithri Chandana Veluri; Noshene Ranjbar (Health Psychology Research)
This scoping review explores the current research on PTSD interventions for Natural Disaster survivors. It includes fourteen randomized control trials (RCTs). The included interventions were, pharmaceuticals, nutraceuticals, herbal supplements, CBT, yoga, narrative exposure therapy, acupuncture stimulation, web-based interventions, and a multimodal art and meditation program. CBT is considered the standard of care for general PTSD treatment and was also found to be effective for the treatment of natural disaster-related PTSD symptoms. However, higher-level clinical evidence is needed. There are inconsistencies with the use of pharmaceuticals, nutraceuticals, and herbal supplements, while there is insufficient clinical evidence to effectively determine the efficacy of yoga, acupuncture, art, and narrative exposure therapies. Factors like the availability of resources, cultural sensitivity, and values and preferences impact the effectiveness of interventions used to treat PTSD in natural disaster survivors. Clinical studies in this field need to be further expanded regardless of the study type